Long-term consequences of adolescent cannabinoid exposure in adult psychopathology - Renard, Justine; Krebs, Marie-Odile; Le Pen, Gwenaëlle; Jay, Thérèse M. (Frontiers in Neuroscience, 2014)
Marijuana is the most widely used illicit drug among adolescents and young adults. Unique cognitive, emotional, and social changes occur during this critical period of development from childhood into adulthood. The adolescent brain is in a state of transition and differs from the adult brain with respect to both anatomy (e.g., neuronal connections and morphology) and neurochemistry (e.g., dopamine, GABA, and glutamate). These changes are thought to support the emergence of adult cerebral processes and behaviors. The endocannabinoid system plays an important role in development by acting on synaptic plasticity, neuronal cell proliferation, migration, and differentiation. Delta-9-tetrahydrocanabinol (THC), the principal psychoactive component in marijuana, acts as an agonist of the cannabinoid type 1 receptor (CB1R). Thus, over-activation of the endocannabinoid system by chronic exposure to CB1R agonists (e.g. THC, CP-55,940, and WIN55,212-2) during adolescence can dramatically alter brain maturation and cause long-lasting neurobiological changes that ultimately affect the function and behavior of the adult brain. Indeed, emerging evidence from both human and animal studies demonstrates that early-onset marijuana use has long-lasting consequences on cognition; moreover, in humans, this use is associated with a two-fold increase in the risk of developing a psychotic disorder. Here, we review the relationship between cannabinoid exposure during adolescence and the increased risk of neuropsychiatric disorders, focusing on both clinical and animal studies.